Предмет: Алгебра,
автор: E1315
(х в квадрате - 2х) все в квадрате + (х в квадрате - 2х) = 12
Ответы
Автор ответа:
0
(x^2 - 2x)^2 + (x^2 - 2x) - 12 = 0
Замена переменной (x^2 - 2x) = a (или любая буква которая нравится)
Получаем
а^2 + a - 12 = 0
D= b^2 - 4ac = 1 - 4*(-12) = 49
a1= (-1 + 7)/2=3
a2= (-1 - 7)/2=-4
Обратная замена
(x^2 - 2x)=3
x^2 - 2x - 3=0
D=4 + 12=16
x1= (2 + 4)/2=3
x2=(2-4)/2=-1
или
(x^2 - 2x)=-4
x^2 - 2x +4=0
D=4-16 < 0 - нет корней
Ответ -1 и 3
Похожие вопросы
Предмет: География,
автор: suleymanovasaida3
Предмет: Қазақ тiлi,
автор: aigerimbisenbaevaa
Предмет: История,
автор: mkirienkott2
Предмет: Математика,
автор: 79030953463
Предмет: Физика,
автор: Аноним